Software Implementation and Design of Information Encryption Algorithm Based on DNA Nano Self-Assembled Sensor Array - Li, Caixia (Journal of sensors, 2021)
In the field of information security, DNA cryptography based on DNA molecular configuration and special recognition mechanism between molecules has developed rapidly. DNA molecules have great development potential in the field of information security technology such as information encryption, hiding and authentication, which provides a new way for the development of modern cryptography. The nodes of traditional sensor networks are mostly distributed in the form of a net with strong openness. In the process of node data transmission, the information is likely to be stolen, tampered with, and destroyed at any time. In this paper, an information encryption method based on DNA nano self-assembled sensor technology is proposed, and the encryption software based on DNA nano self-assembled sensor array is designed. The information encryption algorithm is designed, tested, simulated and analysed, and compared with other designs. The simulation results show that the encryption algorithm system based on DNA nano self-assembled sensor array has good function and excellent performance, can fully meet the requirements of network real-time encryption, has good feasibility and security, and reveals the great application potential of DNA molecules in the field of information security.